The impacts of sarcopenia and obesity on physical performance in the elderly. Issue 3 (May 2015) - Chang, Ching-I; Huang, Kuo-Chin; Chan, Ding-Cheng; Wu, Chih-Hsing; Lin, Cheng-Chieh; Hsiung, Chao A.; Hsu, Chih-Cheng; Chen, Ching-Yu
Summary Objective/Background The current definition of sarcopenic obesity in the elderly does not seem to take the ageing difference of body composition into sufficient consideration. The study accordingly attempted to better define sarcopenia/obesity based on various references, and the impacts of sarcopenia/obesity on elderly physical performance were also examined. Design and methods 2629 elderly subjects (age ≧65) and 998 young adults were recruited for Sarcopenia and Translational Ageing Research in Taiwan (START). For each eligible subject, body composition was measured by bio-impedance analysis and physical performance, including upper and lower extremity function, was examined. The thresholds of sarcopenic obesity were defined as a value at two standard deviations from the gender-specific means of the young population or at the adopted value of our elderly population. Results Compared to the young adults, the elderly subjects reported a lower appendicular skeletal muscle index (ASMI, kg/m2) and a significantly higher fat percentage (%). From three different criteria, thresholds of obesity or sarcopenia were 31.41%, 30.16%, 30.64% (fat percentage) or 6.76 kg/m2, 7.36 kg/m2, 7.09 kg/m2 (ASMI) for men and 39.17%, 41.43%, 43.25% or 5.28 kg/m2, 5.74 kg/m2, 5.70 kg/m2 for women. The elderly subjects were classified into four groups. With covariates adjusted, the "sarcopenia only, " "obesity only, " and "sarcopenic obesity" elderly subjects were worse than their normal counterparts in physical performance (all p < 0.05 except for the handgrip strength compared in groups 1 and 3). Conclusions Sarcopenic obesity seems to exert a synergistic impact on elderly physical performance. Body composition should be an essential part in geriatric assessment and elderly care.